PESAN PERSUASI "PERIKSA PAYUDARA SENDIRI (SADARI)" DAN PERILAKU DETEKSI DINI PENCEGAHAN KANKER PAYUDARA FOLLOWERS INSTAGRAM @ICCC.ID - Ghariza Fathia (2022)
Breast cancer is the number one malignant disease that attacks women. Unfortunately, most women come to the hospital at an advanced stage. Therefore, it is necessary to have public knowledge about early detection of breast cancer to prevent and facilitate breast cancer treatment. Advances in technology today facilitate the dissemination of information, including information about health. Social media can be used to invite people to be aware of the importance of maintaining health. One of the social media that is often used by people is Instagram. The Cancer Care Indonesia Community or better known as ICCC is one of the cancer care communities that uses Instagram as a place to socialize with their followers. Aware of the importance of detecting breast cancer early, ICCC shares information on how to do a breast self-examination or realize it on their Instagram account @iccc.id. This study aims to describe persuasive messages and conscious behavior, as well as to prove the effect of the persuasive message "Breast Self-Examination (BSE)" on the behavior of breast cancer early detection of Instagram followers @iccc.id, with a research sample of 100 respondents. This research uses quantitative research with explanative research methods. The results of the study prove that if there is an effect of the persuasive message "Breast Self-Examination (BSE)" on the behavior of early detection of breast cancer prevention for Instagram followers @iccc.id with the results of hypothesis testing using the t test, the results are t count 16.04 > t table 1.987 so that H0 is rejected and Ha is accepted. So it can be concluded that the persuasive message "Breast Self-Examination (BSE)" on the Instagram account @iccc.id has a significant effect on the behavior of early detection of breast cancer prevention for Instagram followers @iccc.id.